Quality of Life After Deep Brain Stimulation of Pediatric Patients with Dyskinetic Cerebral Palsy: A Prospective, Single‐Arm, Multicenter Study with a Subsequent Randomized Double‐Blind Crossover (STIM‐CP). Issue 4 (29th December 2021) - Koy, Anne; Kühn, Andrea A.; Huebl, Julius; Schneider, Gerd‐Helge; van Riesen, Anne K.; Eckenweiler, Matthias; Rensing‐Zimmermann, Cornelia; Coenen, Volker Arnd; Krauss, Joachim K.; Saryyeva, Assel; Hartmann, Hans; Haeussler, Martin; et al.
Abstract: Background: Patients with dyskinetic cerebral palsy are often severely impaired with limited treatment options. The effects of deep brain stimulation (DBS) are less pronounced than those in inherited dystonia but can be associated with favorable quality of life outcomes even in patients without changes in dystonia severity. Objective: The aim is to assess DBS effects in pediatric patients with pharmacorefractory dyskinetic cerebral palsy with focus on quality of life. Methods: The method used is a prospective, single‐arm, multicenter study. The primary endpoint is improvement in quality of life (CPCHILD [Caregiver Priorities & Child Health Index of Life with Disabilities]) from baseline to 12 months under therapeutic stimulation. The main key secondary outcomes are changes in Burke‐Fahn‐Marsden Dystonia Rating Scale, Dyskinesia Impairment Scale, Gross Motor Function Measure‐66, Canadian Occupational Performance Measure (COPM), and Short‐Form (SF)‐36. After 12 months, patients were randomly assigned to a blinded crossover to receive active or sham stimulation for 24 hours each. Severity of dystonia and chorea were blindly rated. Safety was assessed throughout. The trial was registered at ClinicalTrials.gov, number NCT02097693. Results: Sixteen patients (age: 13.4 ± 2.9 years) were recruited by seven clinical sites. Primary outcome at 12‐month follow‐up is as follows: mean CPCHILD increased by 4.2 ± 10.4 points (95% CI [confidence interval] –1.3 to 9.7; P  = 0.125); among secondary outcomes: improvement in COPM performance measure of 1.1 ± 1.5 points (95% CI 0.2 to 1.9; P  = 0.02) and in the SF‐36 physical health component by 5.1 ± 6.2 points (95% CI 0.7 to 9.6; P  = 0.028). Otherwise, there are no significant changes. Conclusion: Evidence to recommend DBS as routine treatment to improve quality of life in pediatric patients with dyskinetic cerebral palsy is not yet sufficient. Extended follow‐up in larger cohorts will determine the impact of DBS further to guide treatment decisions in these often severely disabled patients. © 2021 The Authors. Movement Disorders published by Wiley Periodicals LLC on behalf of International Parkinson and Movement Disorder Society Abstract : Koy et al report the first prospective multicenter, monitored study on deep brain stimulation in pediatric patients with dyskinetic cerebral palsy. The change in quality of life (primary outcome) was heterogeneous and did not reach statistical significance after 12 months of chronic stimulation.